1999
DOI: 10.1046/j.1365-2672.1999.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cryptosporidium oocysts in water: techniques for generating precise recovery data

Abstract: ON AS A ND C. R . F RI C KE R. 1999. When determining the recovery efficiency of a procedure for the detection of Cryptosporidium or the removal efficiency of a treatment process, it is necessary to accurately enumerate a 'seed dose'. Conventional techniques for this are highly variable and consequently, can result in misleading data. In this study, a flow cytometric method was developed for the production of suspensions of Cryptosporidium oocysts in which the number of organisms could be precisely determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 14 publications
2
25
0
1
Order By: Relevance
“…The use of this new technology application yields counts of Cryptosporidium that are at least equivalent to the conventional methods. The results reported in the present study are in agreement with those of other studies that have compared the ability of Cryptosporidium detection by the ChemScanRDI (7,20,21) in drinking waters. Our study compared the capacity of both cytometers for oocyst counts in polluted samples (such as raw sewage effluents) to verify the correct performance in this kind of environmental samples.…”
Section: Discussionsupporting
confidence: 93%
“…The use of this new technology application yields counts of Cryptosporidium that are at least equivalent to the conventional methods. The results reported in the present study are in agreement with those of other studies that have compared the ability of Cryptosporidium detection by the ChemScanRDI (7,20,21) in drinking waters. Our study compared the capacity of both cytometers for oocyst counts in polluted samples (such as raw sewage effluents) to verify the correct performance in this kind of environmental samples.…”
Section: Discussionsupporting
confidence: 93%
“…pGEMT plasmid copy number per microlitre of DNA Mean percentage of RSD (Reynolds et al, 1999), the DNA extraction efficiency (based on 375 18S rRNA ddPCR) was higher and was on average 75% and 72% at 376 the 18S and actin loci, respectively (Table 2). Therefore at a nomi-377 nal oocyst count of five oocysts/reaction, the adjusted qPCR read-378 ings were 3.5 and 4.0 oocysts, respectively (Table 1).…”
Section: Tablementioning
confidence: 99%
“…For the two loci, the range was 0.76-1.64, but the aver-385 age ratios were close to one for both loci. shown to be more reliable (Reynolds et al, 1999 for both loci with the exception of human isolate HC05 (Table 3).…”
mentioning
confidence: 99%
“…It has been reported that oocysts are unevenly distributed within stock suspensions (4,9). To correct for this deficiency of the method in the future, it is recommended that oocyst seed doses be flow enumerated and sorted directly into the IMS Leighton tubes (19). Despite this, however, the seeded value used to evaluate IMS-FA and IMS-PCR recovery efficiencies in this study were at or below the nominal oocyst seed dose of interest.…”
Section: Resultsmentioning
confidence: 83%
“…The reported IMS-FA recovery rates for oocysts seeded into previously concentrated water pellets of various turbidities have been 62 to 100% (oocyst seed density as determined by dilution, 36 to 976) (20), 55.9 to 83.1% (oocyst seed density as determined by dilution, 89.1 to 98.7) (17), 68 to 83% (oocyst seed density as determined by dilution, 525 to 870) (3), and 84.3% (oocyst seed density as determined by flow cytometry, 100) (19). In an additional study, in which oocysts were seeded into 10-liter grab samples of various turbidities, the reported recoveries ranged from Ͻ1.7 to 56.6% (oocyst seed densities, 1,615 and 2,880) (8).…”
mentioning
confidence: 99%